(untitled) (American Journal of Technology and Applied Sciences, 2025)
Background. The Aral Sea region of Uzbekistan is exposed to combined air, water and soil pollution that has intensified over the past 15 years. Spatially explicit, temporally resolved descriptions are required for evidence-based environmental policy. Objective. To quantify the 2010–2025 evolution of pollution at district resolution across 25 administrative units of Karakalpakstan and Khorezm, and to derive a 2030 outlook. Methods. Annual PM10/PM2.5, surface-water TDS and CCME WQI, and soil heavy-metal and organochlorine concentrations were compiled. Joinpoint regression identified change-points; Mann–Kendall and Sen’s slope tested trends. A no-additional-mitigation 2030 outlook was generated with 95 % prediction intervals. Results. PM10 rose 8–12 % (Moynak +27 %); Amu Darya TDS rose 50 % to 1.4 g/L; Moynak soil ECe rose 42 %. Regional CPI rose from 0.38 to 0.44 (+15.8 %), with post-2017 acceleration (APC +1.4 %, p < 0.001). The 2030 outlook is CPI = 0.51 (95 % PI: 0.48–0.54), with seven districts in ’high’ or ’critical’ bands. Conclusions. The region is on a clear deterioration trajectory; targeted, district-resolved mitigation is urgent.